REALISASI KESANTUNAN PADA ACARA TALK SHOW “MATA NAJWA” - Widya Gusvita (Sekolah Pascasarjana Universitas Pendidikan Indonesia, 2016)
This study aimed to describe the use of politeness language in the communication process in the mass media television. The process of communication is not only considering the language according to the rules of grammar, but also got to see decency and civility in its use. The method used in this research is qualitative descriptive. The data collection technique used is the technique see and record. The data analysis technique used is dishonest. Source of research data be recorded impressions talk show